Propuesta de mejora para la planta de agua potable de la empresa Fertilizantes Colombianos S.A. (2017)
In the following grade work developed a proposal for improvement for the drinking water plant of the company Fertilizantes Colombianos S.A. A total diagnosis of the plant was carried out, in which the current state of the equipment, the infrastructure and the chemical inputs used in the treatment were examined. By means of characterizations carried out by an external laboratory, samples of water taken from the water source and the product of the plant, both in summer and winter conditions, verified the non-compliance with resolution 2115 of 2007 and established the critical parameters of process as the son of turbidity, color and iron, which was sought to improve in this project, so it was proposed 3 alternatives, of these was chosen the most convenient through a selection matrix.